Analysis of masonry arches reinforced with FRP sheets: experimental results and numerical evaluations - Galassi Stefano (MATEC Web of Conferences, 2018)
In recent years fiber-reinforced polymers (FRP) have been widely used for strengthening masonry structures. In particular, in the case of masonry arches, the use of FRP sheets increases load-bearing capacity by limiting or preventing the occurrence of tensile cracks that could activate collapse mechanisms. The effectiveness of the strengthening intervention depends on the bond between FRP and substrate, due to the shear and normal stresses that occur in the bond interface, so much so that the typical failure mode of an arch reinforced with narrow FRP sheets at the intrados is exactly delamination. In this paper a predictive numerical procedure of the combined mode I and mode II failure is proposed. Numerical results provided by this procedure are compared to the experimental results on in-scale arch models taken from a recent work of the author.